Kesejarahan Teks pada Naskah Syair Kupu-Kupu - Delima Novitasari; Asep Yudha Wirajaya (Perpustakaan Nasional RI, 2021)
Manuscript Syair Kupu-Kupu (hereinafter referred to as SKK) is one of the manuscripts that fall into the category of symbolic poetry. This manuscript stored at Staatsbibliothek zu Berlin with the Schoemann V 40 manuscript code. SKK has three version of texts. This manuscript does not have a colophon containing information about the manuscript. SKK manuscripts is included in the category of symbolic poetry because the contents of the SKK text are assumed to represent past events written using animal and plant symbols as character names. This characteristic of symbolic poetry described by GL Koster in his dissertation research. The research on the SKK manuscrips was carried out to determine the history of the emergence of symbolic poetry through the information contained in the text. The theories used in this research are codicology and textology theories. Codicological theory is used to describe the text. Textological theory is used to analyze the history of the SKK text and the reasons for the emergence of symbolic verses. The result of the research on the SKK manuscript was that the SKK manuscript was written at the request of a manuscript collector from Germany named Carl Schoemann while in the Dutch East Indies. In addition, the emergence of symbolic poetry in the Malay region is due to the concept in the Malay community to hide things that are considered taboo to be told. This is in accordance with the agreement of the first Malay king with his people in Malay History.